Amnesiopolis: From Mietskaserne to Wohnungsbauserie 70 in East Berlin's Northeast. Issue 2 (9th July 2014) - Rubin, Eli
<x content-type="archive" xml:space="preserve">Abstract</x> On April 11, 1977, near a small village northeast of Berlin called Marzahn, construction teams from the Volkseigener Betrieb (VEB) Tiefbau Berlin began digging the first foundation for what became the largest construction site and the largest prefabricated housing settlement (Plattenbausiedlung) not just in the German Democratic Republic (GDR), but in all of Europe (see Figure 1). An army of more than 6, 000 workers arrived, and over the course of the next decade, built more than 200, 000 apartments in Marzahn and the surrounding areas of the northeast edge of Berlin. These came to house more than 400, 000 residents, who moved there from the older neighborhoods of East Berlin and from all over the GDR.